ANALISIS PERANAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN ALAT-ALAT KESEHATAN DALAM RANGKA MEMENUHI KEBUTUHAN PELAYANAN RAWAT INAP (STUDI KASUS PADA RUMAH SAKIT UMUM BAHTERAMAS PROVINSI SULAWESI TENGGARA) - Achmad, Nur Azizah (JURNAL AKUNTANSI, 2016)
This research aims to: (1) to find out the sufficiency accounting information system inventory health equipment in hospital. (2) to find out the role of accounting information system inventory health equipment to meet the needs of the inpatient. The method used is descriptive analysis method.            The results of the research done indicates that: (1) accounting information system inventory health equipment in General Hospital Bahteramas The Province Of South East Sulawesi adequate, (2) the accounting information system inventory health equipment turned out to be instrumental to the needs of inpatient services at the hospital Bahteramas the province of Southeast Sulawesi. To facilitate the creation of regular reports about data preparation, facilitate investigation proof inventory, able to present the data as an ingredient in the manufacture of planning and budgeting it is recommended that the accounting information system application BLUD that has been used by hospitals in other provinces.Key words: Accounting Information Systems and Inventory Health Equipment